Lasso peptides sviceucin and siamycin I exhibit anti-virulence activity and restore vancomycin effectiveness in vancomycin-resistant pathogens - Abdelhakim Boudrioua; Benjamin Baëtz; Solenn Desmadril; Christophe Goulard; Anne-Claire Groo; Carine Lombard; Sabrina Gueulle; Marie Marugan; Aurélie Malzert-Fréon; Axel Hartke; Yanyan Li; Caroline Giraud (iScience)
Summary: Antibiotic resistance is a major threat to human health and new drugs are urgently needed. Ideally, these drugs should have several cellular targets in pathogens, decreasing the risk of resistance development. We show here that two natural ribosomally synthesized lasso peptides (LPs), sviceucin and siamycin I, (1) abolish bacterial virulence of pathogenic enterococci, (2) restore vancomycin clinical susceptibility of vancomycin-resistant (VR) enterococci in vitro and in a surrogate animal model, and (3) re-sensitize VR Staphylococcus aureus. Mode of action (MoA) analyses showed that they do so by inhibiting the histidine kinases (HKs) FsrC and VanS controlling these phenotypes. Strains resistant to the vancomycin/LP combination were difficult to obtain, and were still fully susceptible to the anti-virulence effect of the LPs, highlighting the advantage of multiple targets. Together with the highly sought-after MoA as HK inhibitors, such properties make these lasso peptides promising candidates for the development of next generation antibiotics.